Le forme felici di Kafka: Distorcere l'umano, redimere la creatura (Balthazar, 2024)
The article analyses and comments a famous sentence marking the essay that Walter Benjamin devoted to Kafka in 1934 for the 10th anniversary of Kafka’s death: noting how distortion is the distinctive feature of Kafka’s writing, Benjamin takes as its paradigm the «little hunchback» from a famous German folksong, concluding however that «he will disappear with the coming of the Messiah, who (a great rabbi once said) will not wish to change the world by force but will merely make a slight adjustment in it». In the form of this disappearing and of this «adjustment» lies the meaning of Kafka’s messianic project: does it implies a straightening up of the hump? And if not, what form will redemption take?
Keywords: Franz Kafka; Walter Benjamin; Distortion; Redemption; Perspectival Change